ANALISIS PENGETAHUAN DAN PENGGUNAAN WEBSITE JAKEVO PADA MASYAKAT KELURAHAN PENGGILINGAN DENGAN METODE EUCS - Risma Linda; Siti Faizah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the level of knowledge and usage of the Jakarta Evolution (JAKEVO) website among the residents of Kelurahan Penggilingan. JAKEVO is an online licensing service provided by the Jakarta Provincial Government. This research uses a descriptive quantitative method with a survey approach and data analysis using the End-User Computing Satisfaction (EUCS) method, which includes five dimensions: Content, Accuracy, Format, Ease of Use, and Timeliness. Data was collected through questionnaires distributed to 100 purposively selected respondents. The results show that most of the community is aware of and has used the JAKEVO website. Validity and reliability tests indicate that all items are valid and reliable, with a Cronbach’s Alpha value of 0.964 for the usage variable. The most dominant dimensions influencing user satisfaction are Format and Timeliness. However, some users still face challenges in understanding certain features, especially those with low digital literacy. This research recommends increasing public outreach, simplifying the interface, and providing digital training for the community.